1993
DOI: 10.1111/j.1365-2133.1993.tb03336.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin therapy for acne vulgaris: a re-evaluation of the need for measurements of plasma lipids and liver function tests

Abstract: A retrospective analysis of patients receiving isotretinoin for acne was performed, in order to determine the necessity for routine testing of lipid profiles and liver function tests during therapy. Data were analysed from 209 individuals, 113 (69 males, 44 females) of whom had been treated with 1 mg/kg/day, and 96 (67 males, 29 females) with 0.5 mg/kg/day. There were no significant changes in any of the tests of liver function. There were significant elevations in both plasma cholesterol and triglycerides at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 14 publications
4
48
0
2
Order By: Relevance
“…23,25 The most significant lipid elevations were observed in patients who already had elevated baseline laboratory values. 26 There was no correlation between the severity of laboratory value abnormalities and the dosage of isotretinoin. Patients who are overweight or who have increased baseline triglyceride levels are at greater risk for hypertriglyceridemia during treatment, but normal baseline triglyceride levels do not rule out the possibility of developing abnormalities.…”
Section: Lipid and Hepatic Effectsmentioning
confidence: 90%
“…23,25 The most significant lipid elevations were observed in patients who already had elevated baseline laboratory values. 26 There was no correlation between the severity of laboratory value abnormalities and the dosage of isotretinoin. Patients who are overweight or who have increased baseline triglyceride levels are at greater risk for hypertriglyceridemia during treatment, but normal baseline triglyceride levels do not rule out the possibility of developing abnormalities.…”
Section: Lipid and Hepatic Effectsmentioning
confidence: 90%
“…29 In contrast, Barth et al reported no significant changes in liver function tests in a series of 200 patients treated with isotretinoin at a dose of 1 mg/kg/day. 20 In the current study, as the number of patients using Zoretanin was much lower than that of those using Roaccutane®, it was not possible to make a statistical comparison of the clinical side-effects of these two medications. However, when the proportional rates of clinical side-effects were compared, a higher rate was determined in patients using Zoretanin®.…”
Section: Discussionmentioning
confidence: 77%
“…19 Several different studies have demonstrated that there may be increases in cholesterol and triglyceride levels as a result of isotretinoin treatment. 9,18,20,21 Berstad et al applied isotretinoin at a dose of 1 mg/kg/day to 60 patients for 20 weeks and determined an increase of 17% in triglyceride levels. 22 In a study by Lestringant et al, isotretinoin at a dose of 0.2-1.6 mg/kg/day was administered to 140 patients, and a significant increase in triglyceride and cholesterol levels was reported in the sixth week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations